2019
DOI: 10.1021/acs.est.9b03304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microplastics in Soil Ecosystems: Above and Below Ground

Abstract: Highlights:  Microplastics may affect important processes in soil ecosystems.  HDPE, PLA and fibres affected initial growth of perennial ryegrass.  Plant primary production may be affected by microplastics in soil.  Earthworm biomass gain was negatively affected by microplastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
405
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 979 publications
(436 citation statements)
references
References 86 publications
21
405
1
9
Order By: Relevance
“…[19,20]. However, the growth of earthworms is meaningfully different in soil ecosystems, particularly agricultural land, contaminated with microplastics [21]. In addition, it is noteworthy that microplastics are widespread in naturally-occurring Arctic deep-sea sediments [22] and in snow ranging from the Alps to the Arctic [23].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20]. However, the growth of earthworms is meaningfully different in soil ecosystems, particularly agricultural land, contaminated with microplastics [21]. In addition, it is noteworthy that microplastics are widespread in naturally-occurring Arctic deep-sea sediments [22] and in snow ranging from the Alps to the Arctic [23].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of MPs on soil-plant and water-plant systems have started gaining increasing attention recently. MPs in soil matrix can affect the soil properties including soil aggregation, bulk density and water holding capacity and may also affects water properties such as total dissolved and suspended solids, electrical conductivity, pH and dissolved oxygen [3,[5][6]56]. Plants are usually exposed to MPs from the soil matrix and the effect or toxicity they have maybe dependent on plant, type, shape, size and concentration of MPs [1,4].…”
Section: Plantsmentioning
confidence: 99%
“…For terrestrial organisms, soil invertebrates, such as nematodes, collembolan, oligochaeta (e.g. earthworms) and isopods have been studied [1,9,56]. The toxicological effect of MPs on soil organisms have been extensively discussed and reviewed [1,9].…”
Section: Animalsmentioning
confidence: 99%
“…While many studies focus on the impacts of microplastics on fauna, few actually probed their impacts on plants and agriculture. It was found that farmlands contain substantial microplastics because sludge from wastewater and sewage treatment plants is often used as soil additives for agriculture [7]. In fact, wastewater and sewage treatment plants are significant contributors of environmental microplastics through discharge of effluents and sludge containing microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…ic fiber and biodegradable polylactic acid reduced the shoot Lolium perenne) but increased its chlorophylls a and b levels (7). Synthetic fiber and biodegradable polyacetic acid also retarded seed germination though the former was linked to an increase in root biomass.…”
mentioning
confidence: 97%